2013
DOI: 10.2174/092986713804870864
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drug Effects in Schizophrenia: A Review of Longitudinal fMRI Investigations and Neural Interpretations

Abstract: The evidence that antipsychotics improve brain function and reduce symptoms in schizophrenia is unmistakable, but how antipsychotics change brain function is poorly understood, especially within neuronal systems. In this review, we investigated the hypothesized normalization of the functional magnetic resonance imaging (fMRI) blood oxygen level dependent signal in the context of antipsychotic treatment. First, we conducted a systematic PubMed search to identify eight fMRI investigations that met the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 84 publications
(128 reference statements)
2
30
0
Order By: Relevance
“…First, although we examined the impact of medication use, motor‐side effects and smoking status in regards to our findings, we cannot entirely rule‐out their effects on neurovascular coupling, the vasculature and hence the HRF [Friedman et al, ; Leyba et al, ; Roder et al, ]. For example, certain antipsychotic medications (e.g., olanzapine and risperidone) result in cardiovascular abnormalities in both preclinical and human studies [Aboul‐Fotouh and Elgayar, ; Leung et al, ], which may directly affect the HRF [Abbott et al, ; Roder et al, ]. Similarly, HRF may also be influenced by other disease‐related changes to perfusion, metabolism, structure volume loss, neurochemical, or a combination of any of these factors, all of which would impact on current findings.…”
Section: Discussionmentioning
confidence: 99%
“…First, although we examined the impact of medication use, motor‐side effects and smoking status in regards to our findings, we cannot entirely rule‐out their effects on neurovascular coupling, the vasculature and hence the HRF [Friedman et al, ; Leyba et al, ; Roder et al, ]. For example, certain antipsychotic medications (e.g., olanzapine and risperidone) result in cardiovascular abnormalities in both preclinical and human studies [Aboul‐Fotouh and Elgayar, ; Leung et al, ], which may directly affect the HRF [Abbott et al, ; Roder et al, ]. Similarly, HRF may also be influenced by other disease‐related changes to perfusion, metabolism, structure volume loss, neurochemical, or a combination of any of these factors, all of which would impact on current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, few imaging studies of pharmacologically induced cognitive changes exist. Importantly, the existing studies share important limitations in the wide effects of antipsychotics on the brain, which may confound neural changes relevant to cognition with changing symptoms or side-effects (76). Relevant findings include reduced default-mode negative modulation and increased connectivity in the ventral medial PFC during n -back tasks (77), as well as increased activity in the sensory and ventrolateral PFC, and decreased activation in the DLPFC, striatum, and thalamus during visually guided eye saccades (78).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant findings include reduced default-mode negative modulation and increased connectivity in the ventral medial PFC during n -back tasks (77), as well as increased activity in the sensory and ventrolateral PFC, and decreased activation in the DLPFC, striatum, and thalamus during visually guided eye saccades (78). These studies report both neural normalization and denormalization, which may be influenced by cognitive or motor side-effects of the treatments, as well as a general effect of antipsychotics on the BOLD response (76). These confounders should be considered when comparing pharmacological treatment and CRT for cognitive deficits, though they may both provide evidence for the role of prefrontal changes in cognitive improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dopaminergic antagonism generally alters BOLD signal and functional connectivity in healthy subjects, depending on the task paradigms and regions investigated (Abler, Erk, & Walter, ; Brassen et al, ; Honey et al, ; Tost et al, ). These changes are considered to be due to modifications of neuronal activity and cerebral vascular function (Abbott, Jaramillo, Wilcox, & Hamilton, ; Rӧder, Dieleman, van der Veen, & Linden, ). In addition, although the data are limited, studies with unmedicated patients with schizophrenia have also reported decreased or increased large‐scale functional networks (Guo et al, ; Kraguljac et al, ; Lui et al, ).…”
Section: Discussionmentioning
confidence: 99%